2020
DOI: 10.1155/2020/2908108
|View full text |Cite
|
Sign up to set email alerts
|

Fernblock® Upregulates NRF2 Antioxidant Pathway and Protects Keratinocytes from PM2.5-Induced Xenotoxic Stress

Abstract: Humans in modern industrial and postindustrial societies face sustained challenges from environmental pollutants, which can trigger tissue damage from xenotoxic stress through different mechanisms. Thus, the identification and characterization of compounds capable of conferring antioxidant effects and protection against these xenotoxins are warranted. Here, we report that the natural extract of Polypodium leucotomos named Fernblock®, known to reduce aging and oxidative stress induced by solar radiations, upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…An in vivo experiment showed that asiatic acid had a visible effect on doxorubicin (DXR)-induced organ toxicities, showing the best effect at 20 mg/kg by affecting the expression of Nrf2 ( Kamble and Patil, 2018 ). Doxorubicin causes the peroxidation of organs and reduces the activity of innate antioxidant factors ( Sonawane et al, 2018 ) while upregulating the expression of Nrf2 effectively promotes antioxidant activity and protects cells from the damage caused by oxidative stress ( Qi et al, 2017 ; Delgado-Wicke et al, 2020 ). In vivo and in vitro experiments also found that asiatic acid reduced the levels of inflammatory factors (IL-1β ↓, IL-6 ↓) by affecting the Notch signaling pathway, weakened liver and kidney damage, and improved the survival rate in the experimental sepsis mice model ( Yuyun et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…An in vivo experiment showed that asiatic acid had a visible effect on doxorubicin (DXR)-induced organ toxicities, showing the best effect at 20 mg/kg by affecting the expression of Nrf2 ( Kamble and Patil, 2018 ). Doxorubicin causes the peroxidation of organs and reduces the activity of innate antioxidant factors ( Sonawane et al, 2018 ) while upregulating the expression of Nrf2 effectively promotes antioxidant activity and protects cells from the damage caused by oxidative stress ( Qi et al, 2017 ; Delgado-Wicke et al, 2020 ). In vivo and in vitro experiments also found that asiatic acid reduced the levels of inflammatory factors (IL-1β ↓, IL-6 ↓) by affecting the Notch signaling pathway, weakened liver and kidney damage, and improved the survival rate in the experimental sepsis mice model ( Yuyun et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The photoprotection activity of a hydrophilic botanical extract from Polypodium leucotomos , FB, against potential blue light-induced skin damage was also evaluated. FB is an interesting candidate for providing protection against the previously-stated alterations due to its antioxidant and anti-inflammatory properties [ 29 ]. It has been shown to exert an effect on preventing immunosuppression and DNA damage induced by UV and VIS and reducing inflammation, among others [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown how shorter wavelength VIS is also capable of triggering melanin photooxidation and promoting darkening of melanosomes, contributing to the overall development of hyperpigmentation. Our group previously studied the effect of FB on melanin production but no differences were observed in tyrosinase activity, thus we decided to focus on the antioxidant mechanisms in terms of photooxidation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, epidemiological studies showed that the association between traffic-related PM and skin aging traits is not mediated by a systemic effect involving the inhalation of PM and a subsequent pulmonary inflammatory reaction, indicating exposure through the skin surface as the most relevant route (Vierkö tter et al, 2017). We therefore view the increasing number of in vitro studies in which PM is added into the medium of twodimensional cultures to learn about the effects of air pollutants on human skin as difficult to interpret (Delgado-Wicke et al, 2020;Lin et al, 2016;Qiao et al, 2017;Ryu et al, 2019).…”
Section: Air Pollutionmentioning
confidence: 99%